2014
DOI: 10.1590/0001-3765201420130162
|View full text |Cite
|
Sign up to set email alerts
|

First Ediacaran Fauna Occurrence in Northeastern Brazil (Jaibaras Basin, ?Ediacaran-Cambrian): Preliminary Results and Regional Correlation

Abstract: This study reports the first known occurrence of the Ediacaran fauna in northeastern Brazil (at Pacujá Municipality, northwestern state of Ceará) and presents preliminary interpretations of its significance. Regional correlation indicates that the fossils originated in the Jaibaras Basin and that they may represent a new geological system. The depositional environment can be attributed to a fluviomarine system. Nine Ediacaran species can be identified, including members of pandemic groups (e.g., Charniodiscus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Apart of skeletal records of acritarchs 16 18 , calcified or organic-walled macroscopic Cloudina lucianoi 14 , Corumbella werneri 13 and extremely rare conulariids 17 recorded in the Ediacaran Corumbá Group, Mato Grosso do Sul, Brazil, impressions of macroscopically complex, soft-bodied organisms are scarce in South American deposits of this age 22 23 24 . Siliciclastic sedimentary strata preserved in the Neoproterozoic Itajaí Basin, southern Brazil, record poorly preserved impressions assigned to Parvancorina sp., Charniodiscus ?…”
Section: The South American Record Of Ediacaran Macrofossilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart of skeletal records of acritarchs 16 18 , calcified or organic-walled macroscopic Cloudina lucianoi 14 , Corumbella werneri 13 and extremely rare conulariids 17 recorded in the Ediacaran Corumbá Group, Mato Grosso do Sul, Brazil, impressions of macroscopically complex, soft-bodied organisms are scarce in South American deposits of this age 22 23 24 . Siliciclastic sedimentary strata preserved in the Neoproterozoic Itajaí Basin, southern Brazil, record poorly preserved impressions assigned to Parvancorina sp., Charniodiscus ?…”
Section: The South American Record Of Ediacaran Macrofossilsmentioning
confidence: 99%
“…and Cyclomedusa sp 23 . On the other hand, supposed impressions of soft-bodied specimens were reported from a fluvio-marine succession in the probably Cambrian Jaibaras Basin, northeastern Brazil 24 . However, the nature of those “impressions” is still controversial, mainly due to: (a) their extremely poor preservation, (b) the deep weathering of structures and rock matrix, (c) their preservation within a fluvio-marine succession, (d) the low number of structures in the same bedding plane (except for the Jaibaras Basin), in clear contrast with their large abundance in the best known Ediacaran occurrences 4 , (e) their much larger sizes when compared with other well-accepted records, and (f) unreliable depositional ages of the units containing the dubious structures or fossils (especially in the case of the Jaibaras Basin).…”
Section: The South American Record Of Ediacaran Macrofossilsmentioning
confidence: 99%
“…There, limestone-marl rhythmites occur at the base, which pass into dark gray to black, finely laminated, organic-rich limestones, at the top. Barroso et al (2014) reported the occurrence of probable soft-bodied Ediacaran fossils in the overlying Jaibaras Group, similar to the White Sea assemblage, which could assure an Ediacaran age to this unit (560 -542 Ma, Narbonne 2005; Chiglino et al (2015). Fedonkin et al 2007).…”
Section: Ubajara Group: Frecheirinha Formationmentioning
confidence: 84%
“…Por exemplo, a bactéria Acidithiobacillus ferrooxidans, além de ser capaz de crescer a partir da oxidação de enxofre elementar, consegue crescer através da oxidação de Fe +2 , fixando CO 2 e produzindo atp. Devido a esse metabolismo, é um importante organismo modelo para quimiolitotróficos e tem sido estudada e aplicada nas áreas de biotecnologia e bioprospecção (Nemati et al, 1998;Yang et al, 2009). Porém, é um metabolismo extremamente pouco eficiente, uma vez que produz muito pouco atp (diferença muito pequena entre o potencial de redução do par redox Fe +2 /Fe +3 e o aceptor final de elétrons, O 2 /H 2 O) e gasta uma grande quantidade de atp para gerar poder redutor (grande diferença entre o potencial de redução do par redox Fe +2 /Fe +3 e o aceptor final nadp +/ nadph).…”
Section: Bactéria Reaçãounclassified